Identification of Altered Developmental Pathways in Human Juvenile HD iPSC With 71Q and 109Q Using Transcriptome Profiling - Świtońska, Karolina; Szlachcic, Wojciech J.; Handschuh, Luiza; Wojciechowski, Paweł; Marczak, Łukasz; Stelmaszczuk, Michał; Figlerowicz, Marek; Figiel, Maciej (Frontiers in Cellular Neuroscience, 2019)
In Huntington disease (HD) subtle symptoms in patients may occur years or even decades prior to diagnosis. HD changes at a molecular level may begin as early as in cells that are non-lineage committed such as stem cells or HD patients induced pluripotent stem cells (iPSCs) offering opportunity to enhance the understanding of the HD pathogenesis. In addition, juvenile HD non-linage committed cells were previously not directly investigated in detail by RNA-seq. In the present manuscript, we define the early HD and juvenile HD transcriptional alterations using 6 human HD iPS cell lines from two patients, one with 71 CAGs and one with 109 CAG repeats. We identified 107 (6 HD lines), 198 (3 HD71Q lines) and 217 (3 HD109Q lines) significantly dysregulated mRNAs in each comparison group. The analyses showed that many of dysregulated transcripts in HD109Q iPSC lines are involved in DNA damage response and apoptosis, such as CCND1, CDKN1A, TP53, BAX, TNFRSF10B, TNFRSF10C, TNFRSF10D, DDB2, PLCB1, PRKCQ, HSH2D, ZMAT3, PLK2, and RPS27L. Most of them were identified as downregulated and their proteins are direct interactors with TP53. HTT probably alters the level of several TP53 interactors influencing apoptosis. This may lead to accumulation of an excessive number of progenitor cells and potential disruption of cell differentiation and production of mature neurons. In addition, HTT effects on cell polarization also demonstrated in the analysis may result in a generation of incorrect progenitors. Bioinformatics analysis of transcripts dysregulated in HD71Q iPSC lines showed that several of them act as transcription regulators during the early multicellular stages of development, such as ZFP57, PIWIL2, HIST1H3C, and HIST1H2BB. Significant upregulation of most of these transcripts may lead to a global increase in expression level of genes involved in pathways critical for embryogenesis and early neural development. In addition, MS analysis revealed altered levels of TP53 and ZFP30 proteins reflecting the functional significance of dysregulated mRNA levels of these proteins which were associated with apoptosis and DNA binding. Our finding very well corresponds to the fact that mutation in the HTT gene may cause precocious neurogenesis and identifies pathways likely disrupted during development.